The development of entire body risk asssessment (ENBORA) method for work related musculoskeletal disorders (WMSDs) - Abdul Rahman, Syahrul Aziana (2018)
The observational method remain to be the most widely used method for assessing Workrelated Musculoskeletal Disorders (WMSDs) because it is inexpensive and practical in field data collection. However, several observational methods that are currently available only focus on assessing physical risk factors especially in terms ofthe diversity of body postures which do not encompass other factors of WMSDs including psychosocial risk factors, work organisational risk factors and individual risk factors. In addition, some of the existing methods mainly not focused on reliability and validity test during the development process. In order to improve these limitations, this study aims to deve lop a new observational method called the Entire Body Risk Assessment (ENBORA) method and to determine the reliability and validity of the ENBORA method. The study was conducted in three stages which include the development of ENBORA system components, the development ofthe ENBORA checklist (prototype), and psychometrics evaluation. In reliability testing, very good agreement was obtained for inter-observer reliability. During the training session, the majority of the participants agreed that it was easy to understand and use the ENBORA at work. In validity testing, since the ENBORA method was developed specifically for workers who work using their entire body parts, the highest risk scores were obtained by cleaners and supermarket workers in contrast to office workers according to the ENBORA assessment. The final version ofENBORA was useful for assessing the tasks in many industries as it covers the assessment of the entire body and assesses the physical, psychosocial, work organizational and individual risk factors that lead to WMSDs.